GRAMMATICAL EQUIVALENCE IN TRANSLATING RUSSIAN ADJECTIVES AND ADVERBS INTO ENGLISH - Slepovitch, Viktor (Vertimo studijos, 2017)
Grammatical equivalence in translation is both a subject of research and an important issue of teaching. Grammatical choices are especially hard in the process of translating from one’s mother tongue into a foreign language. This paper discusses some of the specifics of achieving grammatical equivalence in translating adjectives and adverbs from Russian (native source language) into English (foreign target language) based on the author’s translating and teaching experience reflected in his publications in this field of studies.